Characterization of the Soil Prokaryotic Community With Respect to Time and Fertilization With Animal Waste–Based Digestate in a Humid Continental Climate - Suproniene, Skaidre; Doyeni, Modupe Olufemi; Viti, Carlo; Tilvikiene, Vita; Pini, Francesco (Frontiers in Environmental Science, 2022)
There is a renewed global awareness to improve soil health through the intensification and management of organic inputs such as the application of animal waste-based digestate and other types of organic fertilizers to the soil. The objective of this study was to evaluate the influence of different types of animal waste-based digestate application on soil prokaryotic diversity and composition in an agricultural cropping system over a period of three years, cultivated with three different annual cereal crops (spring wheat, triticale and barley). Treatments were laid out in a randomized design with five conditions (three replicates per condition): fertilizer treatments included three different types of digestate (pig manure, chicken manure and cow manure digestates), synthetic mineral nitrogen and unfertilized control. Prokaryotic soil communities were characterized by Illumina MiSeq sequencing. The three most abundant phyla identified were Actinobacteria, Acidobacteria and Proteobacteria which accounted for over 55% of the total prokaryotic community. Other phylogenetic groups such as Verrucomicrobia and Bacteroidetes were also identified as part of the native soil microbiota. It was observed that the period of digestate application did not significantly influence the prokaryotic diversity in the soil. On the contrary, sampling time was a major factor in driving the β-diversity. Our study showed that the richness and diversity of the soil prokaryotic community was not affected by the digestate application, while other factors such as the yearly crop varieties and seasonal/climate changes were the major contributors in differentiating the prokaryotic community composition over time.